Bahasa Inggris - Adiprabowo, Vani Dias; Wibowo, Marsiana (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Stunting is a serious health problem in the Special Region of Yogyakarta (DIY). This is evidenced by the prevalence of stunting in DIY according to the 2021 Indonesian Nutritional Status Survey (SSGI) of 17.3 percent. This figure shows that DIY is ranked third lowest in Indonesia after Bali at 10.9 percent and DKI Jakarta at 16.8 percent. The importance of stunting health literacy based on short film media produced by the DIY Public Health Department (Dinkes) is one of the alternatives and solutions to increase understanding related to stunting. Short film media about stunting has the power to convey relevant health messages to the public. This study aims to obtain a deeper understanding of stunting prevention through health literacy in a short film, Salah Kaprah, produced by the DIY Public Health Department. Qualitative research methods with the research stages are determining the focus of research, data collection, and data analysis. The results showed that the disease-related narrative is still considered dangerous. The disease narrative becomes harmless when delivered by health workers. The role of health workers is central and important to carry out literacy in tackling hoax disease-related issues.